The evolution of the earnings distribution in a volatile economy: Evidence from Argentina - Andrés Blanco; Bernardo Diaz de Astarloa; Andres Drenik; Christian Moser; Danilo R. Trupkin (Quantitative Economics, 2022)
This paper studies earnings inequality and dynamics in Argentina between 1996 and 2015. Following the 2001-2002 crisis, the Argentine economy transitioned from a low- to a high-inflation regime, while collective bargaining and the minimum wage gained influence. This transition was associated with a persistent decrease in earnings dispersion and cyclical movements in higher-order moments of the distribution of earnings changes. To shed light on the changing nature of wage rigidity during this period, we develop a new method to estimate regular-wage processes. As the Argentine economy transitioned from low to high inflation, the monthly frequency of regular-wage changes almost doubled, while the distribution of regular-wage changes morphed from having a mode around zero and positive skewness to having a positive mode and more symmetric tails.
Keywords: E24; E31; J31; 330; Earnings inequality; earnings dynamics; mobility; higher-order moments; inflation; wage rigidity; administrative data; survey data